2016
DOI: 10.4103/0972-9941.169982
|View full text |Cite
|
Sign up to set email alerts
|

Gut barrier function and systemic endotoxemia after laparotomy or laparoscopic resection for colon cancer: A prospective randomized study

Abstract: PURPOSE:The gut barrier is altered in certain pathologic conditions (shock, trauma, or surgical stress), resulting in bacterial and/or endotoxin translocation from the gut lumen into the systemic circulation. In this prospective randomized study, we investigated the effect of surgery on intestinal permeability (IP) and endotoxemia in patients undergoing elective colectomy for colon cancer by comparing the laparoscopic with the open approach.PATIENTS AND METHODS:A hundred twenty-three consecutive patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Systemic inflammatory response has been proven to be induced by gut microbiome-driving LPS with surgery-induced intestinal barrier dysfunction (Rhee, 2014 ; Schietroma et al, 2016 ). According to a trial that was included in our study, the level of serum LPS showed an association with the incidence of POCD (Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic inflammatory response has been proven to be induced by gut microbiome-driving LPS with surgery-induced intestinal barrier dysfunction (Rhee, 2014 ; Schietroma et al, 2016 ). According to a trial that was included in our study, the level of serum LPS showed an association with the incidence of POCD (Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of systemic inflammatory response during the early postoperative period improves postoperative cognitive function, reducing the incidence of POCD in the elderly (Zhang et al, 2018 ). Alarmins were released from the surgical trauma tissue injury or secreted by stimulated leukocytes and epithelial cells, such as high-mobility histone 1, neutrophils, and monocyte cytoplasmic proteins S100A8 and S100A9, as well as systemic endotoxemia, which in turn activate the inflammatory pathway, leading to the release of pro-inflammatory cytokines and anti-inflammatory cytokines, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, IL-10, and so on (Chan et al, 2012 ; Schietroma et al, 2013 , 2016 ). After that, the peripheral inflammatory cytokines activate and compromise with the blood–brain barrier (BBB) integrity, allowing increased infiltration of inflammatory factors and macrophages into the brain (Fu et al, 2014 ), ultimately leading to the damage of neurological function (Leslie, 2017 ; Wei et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%